Resposta :
Resposta:
Explicação passo-a-passo:
Seu exercício: x*2+-6*x+9=0
Seu exercício: Passo a passo:
1*2*x+-6*x+9=0 | Adicione 2*x a -6*x
-4+-6*x+9=0 | -9
-4*x=-9 | : (-4)
1*x=2.25
Seu exercício: x*2+-3*x=0
Conjunto solução: {2.25}
Seu exercício: Passo a passo:
1*2*x+-3*x=0 | Adicione 2*x a -3*x
2*x+-3*x=0 | : (-1)
1*x=0
Conjunto solução: {0}
Seu exercício: -1*x*2+12*x+-20=0
Seu exercício: Passo a passo:
-1*2*x+12*x+-20=0 | Adicione -2*x a 12*x
10+12*x+-20=0 | +20
10*x=20 | : 10
1*x=2
Conjunto solução: {2}